Challenges Facing Antiretroviral Medication Adherence among People Living With Hiv/Aids. A Case of Dodoma City and Kongwa District in Tanzania - Kusunya, Emmanuel (International Journal of Scientific Research and Management (IJSRM), 2022)
The purpose of this study is to analyze the challenges of adherence to antiretroviral therapy (ART) for people living with HIV/AIDS (PLWHIV/AIDS) in Dodoma City and Kongwa District, Tanzania. Data was gathered through document reviews, interviews, and Focus Group Discussions. For this study, 99 respondents were chosen and interviewed as representatives from four hospitals, two health centres, and one dispensary. The quantitative data was obtained using an interview schedule, while the qualitative data was collected using Focus Group Discussions and key informant interviews, and the quantitative data were analyzed using SPSS version 16 software while qualitative data were analyzed by using content analysis. The study revealed five challenges facing PLWHIV/AIDS including the leading stigmatization followed by taking too many tablets, negligence in taking tablets, side effects and the least was side effects impact of medication. The study recommends the following first families, health care facilities, dispensaries, and hospitals must treat PLWHIV/AIDS patients with dignity and respect. Also, global and local HIV/AIDS development partners, notably pharmaceutical companies, should seek ART dosages that allow PLWHIV/AIDS to take only a few medications.